69–78 GHz ESD‐protected SiGe BiCMOS PA with 30 dB automatic level control for mm‐wave 5G applications. Issue 22 (1st November 2018) - Wang, Keping; Qiu, Lei; Wang, Zhigong
Abstract : A silicon–germanium BiCMOS E‐band power amplifier (PA) for millimetre‐waves for Gbit/s data rates in fifth‐generation cellular wireless backhaul networks is presented. A 69–78 GHz transmission‐line PA is demonstrated by integrating an electrostatic discharge (ESD) and a power detector together. To save this area, a transmission‐line‐based power coupler is shared by the ESD and the power detector. The ESD achieves an insertion loss of <1.5 dB in the frequency range of 17–100 GHz. The linear‐in‐dB output characteristic of the power detector is achieved by an exponential voltage convertor. The designed PA measured a maximum gain of 18.6 dB with 3 dB bandwidth of 68.9–78.7 GHz. The input return loss is better than −10 dB from 50 to 81 GHz. It delivers 10 dBm saturated output power at 73.4 GHz. Transmission line pulsing (TLP) measurement result shows that the voltage is clamped below 6 V even under 10 A ESD current.